Immunostimulant Activity of Neem Leaf (A. indica A. Juss) Ethanol Fraction on Tilapia (Oreochromis niloticus) - Putri, Rika; Andayani, Sri; Yuniarti, Ating (Graduate School, Universitas Brawijaya, 2018)
Intensive cultivation of Tilapia with high stock density and continuous artificial feeding will decrease the water quality and increase the growth of pathogenic bacteria. That situation led to the fish stressed so that the fish become the target of bacterial pathogen attacks. Alternatively, the environmental friendly treatment using herbal immunostimulant to solve that problem is required. The herbal in this study used neem leaf (Azadirachta indica A. Juss). The aim of this study was to evaluate ethanol fraction of neem leaf on immunostimulant activity of Oreochromis niloticus. In this study, the extraction method used maceration. Fractionation methods were using Thin Layer Chromatography (TLC) and Column Chromatography (CC). The biological component was analyzed using Phytochemical, FTIR and GC-MS methods. TLC test showed that ethyl acetate: n-hexane (1:1, v/v) result in brightest luminescence colors on the plates of silica gel under UV light (365 nm). The chromatography column from the ethanol extract of neem leaf (A. indica A. Juss) showed that separation of the fraction was done based on the formation of color, which obtained 5 (five) types of fractions. The results of the phytochemical test for the fraction 4 of neem leaf contains two compounds, i.e. flavonoids (+) and triterpenoids (++). The FTIR test showed that fraction 4 of neem leaves contain a class of terpenoid and flavonoid compounds. GCMS test results on fraction 4 of the neem leaves (A. indica A. Juss) obtained the high peak, which has 4 terpenoid compounds, 1 compound of flavonoid, and 1 type of lauric acid. The total leukocyte of the fish test increased after treated with fraction 4 of neem leaf (A. indica A. Juss) compared with control on day 7 after injection, i.e. 25.29 x 104 cells.mL-1.Keywords: fraction, leukocyte, Neem Leaves, Tilapia, Phytochemicals.